Pengembangan Desa Cilibur Sebagai Desa InovatifYang Mandiri Di Kabupaten Brebes - Sutarmin; Kurniawan (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2017)
One of the efforts to boost the local economy is the development of villages with innovation based on local wisdom. The discourse to develop an innovative village already exists in Brebes District. This development effort needs to be focused on one village in advance to serve as a model or reference of other villages that will transform into an innovative village. Cilibur Village was chosen to be developed into an innovative village in the field of cultivation and production of essential oil. Based on the analysis that has been done, it was found that to go to the innovative village, Cilibur Village need science and technology such as: Clove plant rejuvenation, process quality control and essential oil products, good and correct essential oil process, separator design oil and water separator, design Rearrange / modify the cooling pool. Based on the analysis of Quantitative Strategic Planning Matrix (QSPM) the priority of the proposed strategy to develop Cilibur village as innovative village of cultivation and production of essential oil are: (1) Training and assistance; (2) Provision of seed and equipment assistance; (2) Cooperation with other parties; (4) Dedication of equipment, and (5) Search alternative buyer.